Strong Nonlinearity Induced by Coaxial Alignment of Polar Chain and Dense [BO3] Units in CaZn2(BO3)2. Issue 21 (21st March 2022) - Mutailipu, Miriding; Li, Fuming; Jin, Congcong; Yang, Zhihua; Poeppelmeier, Kenneth R.; Pan, Shilie
Abstract: Discovery of new efficient nonlinear optical (NLO) materials with large second‐order nonlinearity for the short‐wave ultraviolet spectral region ( λ P M ≤266 nm, PM=phase‐matching) is still very challenging. Herein, a new beryllium‐free borate CaZn2 (BO3 )2 with Sr2 Be2 B2 O7 (SBBO) double‐layered like configuration was rationally designed, which not only preserves the structural merits but also eliminates the limitations of the SBBO crystal. CaZn2 (BO3 )2 shows a large PM second harmonic generation (SHG) reponse of 3.8×KDP, which is 38 times higher than that of its barium analogue. This enhancement mainly originates from the 1 [Zn2 O6 ]∞ polar chains with a large net dipole moment and [BO3 ] units with a high NLO active density. Our findings show the great significance of the [ZnO4 ] tetrahedra introduced strategy to design beryllium‐free SBBO‐type NLO crystals and also verify the feasibility of using simple non‐isomorphic substitution to induce giant second‐order nonlinearity enhancement. Abstract : A new beryllium‐free borate with double‐layered configuration was rationally designed. It shows a large phase‐matching second harmonic generation reponse, which is 38 times higher than that of its barium analogue. These findings show the great significance of using tetrahedra to design nonlinear optical crystals and also verify the feasibility of using simple non‐isomorphic substitution to induce giant second‐order nonlinearity enhancement.